Implication Equivalent to Negation of Conjunction with Negative/Formulation 1/Proof

From ProofWiki
Jump to navigation Jump to search

Theorem

$p \implies q \dashv \vdash \neg \left({p \land \neg q}\right)$


Proof

We apply the Method of Truth Tables.

As can be seen by inspection, the truth values under the main connectives match for all boolean interpretations.

$\begin{array}{|ccc||ccccc|} \hline p & \implies & q & \neg & (p & \land & \neg & q) \\ \hline F & T & F & T & F & F & T & F \\ F & T & T & T & F & F & F & T \\ T & F & F & F & T & T & T & F \\ T & T & T & T & T & F & F & T \\ \hline \end{array}$

$\blacksquare$


Sources